2018
DOI: 10.1002/acp.3440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of label training and recall order on children's reports of a repeated event

Abstract: Children aged 6-8 (N = 84) were interviewed 1 week after participating in a repeated event. Half received training in labeling episodes of a repeated autobiographical event (Label Training); remaining children practiced talking about the same without label training (Standard Practice). Subsequently, children recalled the target event in two recall order conditions: script for the events followed by a specific instance (Generic-first) or the reverse (Episodic-first). Training effects were modest, but the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Although spontaneous labels by children were rare, only one analogue study has provided insight into children's capabilities to provide effective labels when explicitly instructed to do so. This study found that children aged 6–8 years old were quite good at producing effective labels with appropriate interviewer scaffolding (Brubacher et al ., ). This is an important area for future research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although spontaneous labels by children were rare, only one analogue study has provided insight into children's capabilities to provide effective labels when explicitly instructed to do so. This study found that children aged 6–8 years old were quite good at producing effective labels with appropriate interviewer scaffolding (Brubacher et al ., ). This is an important area for future research.…”
Section: Discussionmentioning
confidence: 97%
“…For example, ‘the time he kissed you’ is not an ideal label if the child was kissed on multiple occurrences. Interviewer‐generated labels are less likely to be specific to one occurrence because the interviewer is naïve about the events in question (Brubacher, Earhart, Roberts, & Powell, ), and non‐unique labels may contribute to greater confusion between events. Interviewers and legal professionals may benefit from guidance about clearly and consistently labelling occurrences of repeated events in order to maximize children's opportunities to provide accurate testimony.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in analog studies nearly all errors about repeated events are "internal" intrusions in which children report experienced details but confuse the occurrence (source). A sample of 455 children collapsed across several studies illustrates this principle (Brubacher, Earhart, Roberts, & Powell, 2018;Brubacher, Glisic, Roberts, & Powell, 2011a;Brubacher, Roberts, & Powell, 2011b;Brubacher, Roberts, & Powell, 2012; with 51 children from unpublished data). Among a group of 4-to 8-year-olds who participated in four events that included some varying details from one occurrence to the next, the mean number of fabricated details (not from the event set) during free recall was just 0.55…”
Section: Children's Narratives Contain Detail Errors and Young Children Have Weaker Filters For Some Types Of Errorsmentioning
confidence: 97%
“…Thus, evidence shows that reliable cues both reinstate the context of the experienced event (Tulving & Thomson, 1973) and provide diagnostic information about specific memories (principle of cue overload; Goh & Lu, 2012;Nairne, 2002). Based on previous applied research, we expected that the use of self-generated cues would facilitate the discrimination of specific instances thereby improving recall while reducing source confusion (Brubacher et al, 2018;Willén et al, 2015).…”
Section: Interviewing Techniques To Facilitate Recall and Reportingmentioning
confidence: 99%